Community Resources and Capacity for Vector Control: Analyzing the Knowledge, Attitude, and Practice (KAP) Gap in Dengue Prevention Readiness - Milanitalia Gadys Rosandy; Candradikusuma, Didi; Sutanto, Heri; Indiastari, Dewi; Budiarti, Niniek; Silvia, Sinta (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Dengue Hemorrhagic Fever (DHF) is still a significant burden to global public health. Successful prevention is a function of community capacity, including locus of control (internal belief in one’s ability) and collective potential to implement prevention. Objectives: The objective of this research was to measure K, A and P with a specific emphasis on examining the degree to which these mentored K, A and P align with community sense-making (meaning), constructed capacity (function), and perceived controllability for making useable space free from vectors. Methods: A cross-sectional design was used, with 102 respondents (mainly women, productive age group and primary education level). Descriptive statistics, Chi-Square test for bivariate analysis and Multivariate Logistic Regression were used to determine independent predictors. Results: A noticeable gap between the KAP was determined. Although the proportion of respondents with favorable attitudes is high (66.7%), that of preventive practices was low (54.9% poor score). There was marginal knowledge (45.1% poor) with a high proportion of critical misconceptions (80.4% incorrect response to key transmission point). On multivariate analysis, significantly associated with good knowledge were education (Junior High vs Primary School) (OR=4.1, p=0.015) and middle income for favorable attitudes (OR=2.9, p=0.041). Notably, neither demographic variable (age, gender, education nor income) showed association with good preventive practice. Conclusion: The poor practice indicates a lack in the ability of DHF preventive activities, i.e. the capacity and collective control despite of high motivation (attitude). That practice was not also predicted by demographics implies that barriers are structural and environmental. Hence, interventions will need to move away from knowledge-based approaches to community mobilization for control and resource movement towards dismantling structural drivers for closing the attitude-practice gap.